The effect of vibroacoustic and light stimulation on fetal health: A review of the literature - Mahla BakhtiyariNasab; Nahid Golmakani (Mashhad University of Medical Sciences, 2018)
Introduction: One of the essential components of the process of prenatal care is the assessment of the fetal health, for which there are several tests. Recently, in some studies, vibroacoustic stimulation and halogen light have also been evaluated as a test for the evaluation of fetal health. This study was conducted with the aim of systematically summarizing recent studies on the effect of stimulation with vibroacoustic and halogen light on the fetus.  Materials and Methods: In this review study, in order to retrieve relevant national and international studies published from 1990 to 2017, the researchers extensively searched the following databases: magirin, irandoc, SID، Google scholar, Scopus, PubMed, and science direct. English keywords included "vibroacoustic" and "halogen light". The papers that had the highest similarity with our review title were entered into the study, and the results were reported. Results: Finally، 15 papers that investigated the effect of halogen light and vibroacoustic stimulation were studied. There was a correlation between fetal heart rate، fetal health assessment, and stimulation with vibroacoustic and halogen light (P<0.05). Conclusion: In general، according to the findings of most studies، there is a correlation between the effect of stimulation with vibroacoustic and halogen light and fetal health and fetal movement tests. Since stimulation with vibroacoustic and halogen light reduce the incidence of non-reactive fetal heart rate، this tool can be used safely and effectively in maternal health assessment centers to improve fetal non-stress test.